2017
DOI: 10.1007/s12272-017-0975-1
|View full text |Cite
|
Sign up to set email alerts
|

The signaling of protease-activated receptor-2 activating peptide-induced contraction in cat esophageal smooth muscle cells

Abstract: Protease-activated receptors (PARs) are a family of G protein-coupled receptors with a unique activation mechanism involving proteolytic cleavage of the extracellular N-terminal domain of the receptor. PAR2 has a contractile effect on esophageal smooth muscle. We investigate the signaling pathways of the PAR2-activating peptide (PAR2-AP) induced contraction in cat esophageal smooth muscle cells. The length of freshly isolated smooth muscle cells and permeabilized cells from feline esophagus were measured by sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…PAR2 has been shown to cause contraction of bronchial, vascular, and esophageal smooth muscles . However, it is not known if PAR2 stimulation can cause contraction of smooth muscles in the prostate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PAR2 has been shown to cause contraction of bronchial, vascular, and esophageal smooth muscles . However, it is not known if PAR2 stimulation can cause contraction of smooth muscles in the prostate.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to determine the function of PAR2, we sought to investigate the effect of PAR2 stimulation in prostatic smooth muscles. Sriwai et al and Ha et al showed that PAR2 activation caused biphasic contraction of gastric and esophageal smooth muscles. However, our study has further characterized the different sources of the intracellular Ca 2+ that cause the distinctive biphasic Ca 2+ flux and demonstrated the involvement of CRAC channels, and not L‐type VDCC, in PAR2‐mediated contraction of prostate smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations